Successful Pharmacologic Treatment of Self-Bloodletting with Factitious Chronic Anemia (Lasthénie de Ferjol Syndrome) with High-Dose Serotonergic Medication: A Case Report - Mestermann, Stefan; Rudtke, Laura; Brazdis, Razvan Marius; Tsaktanis, Thanos; Kornhuber, Johannes; Thürauf, Norbert (Behavioral Sciences, 2024)
Self-induced bloodletting (SBL) is a very rare form of self-injury (SI) seen primarily in adolescents and young adults with personality and eating disorders. It can result in complications like malaise, fatigue, or iron-deficiency anemia (Lasthénie de Ferjol syndrome, LFS), and poses a risk of accidental death or suicide. The condition often goes undetected due to patient concealment. There is no specific treatment established, and pharmacological strategies remain uncertain. We discuss the case of a 22-year-old female patient treated at our Psychiatry and Psychotherapy Department following a suicide attempt via SBL. She self-administered a venous cannula, losing 1.5 L of blood. Diagnosed with iron-deficiency anemia (LFS), she was initially treated with mirtazapine, risperidone, lithium, and later off-label high-dose clomipramine (300 mg/d). Clomipramine significantly reduced her SBL and suicidal thoughts, and her hemoglobin levels re-normalized under iron-substitution therapy. Despite improvement and later discharge, she attempted suicide by SBL again three months later, having stopped clomipramine due to adverse side effects. High-dose escitalopram was administered, leading to a decrease and eventual cessation of her SBL urges. This case demonstrates that patients with SBL/LFS can benefit from high-dose clomipramine or escitalopram. Despite its rarity, the consideration of high-dose serotonergic antidepressants is crucial in psychiatric diagnostics and treatment for patients affected by SBL/LFS.
CRIS-Team Scopus Importer:2024-04-05
Keywords: clomipramine; escitalopram; Lasthénie de Ferjol syndrome; mental health; self-bloodletting; self-harm; self-injury behavior